2019
DOI: 10.3390/antiox8090382
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects of Curcumin: Epigenetic and Antiproliferative Implications for Normal Dermal Fibroblast and Breast Cancer Cells

Abstract: Background: Curcumin is a yellow-orange pigment obtained from the plant Curcuma longa, which is known to exert beneficial effects in several diseases, including cancer. However, at high doses, it may produce toxic and carcinogenic effects in normal cells. In this context, we studied the effects of curcumin on normal human dermal fibroblast (HDF) cells and breast cancer cells (MCF7). Methods: We used cellular viability and growth assays to evaluate the antiproliferative action of curcumin, analyzed the endogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 51 publications
(60 reference statements)
6
33
0
Order By: Relevance
“…Some authors have suggested that the increase in GSH levels in flavonoid treated cells could be related to transactivation of catalytical subunit promoter of the gamma-glutamyl-cysteine synthetase [ 60 ]. GSH is involved in cellular redox regulation as it can be used as a cofactor by enzymes involved in signal transduction [ 61 , 62 ], therefore our results suggest that polyphenol-mediated regulation of GSH levels could modulate cellular response in intestinal cells. Moreover, some flavonoids behave as natural inhibitors of GlxI [ 63 ].…”
Section: Discussionmentioning
confidence: 94%
“…Some authors have suggested that the increase in GSH levels in flavonoid treated cells could be related to transactivation of catalytical subunit promoter of the gamma-glutamyl-cysteine synthetase [ 60 ]. GSH is involved in cellular redox regulation as it can be used as a cofactor by enzymes involved in signal transduction [ 61 , 62 ], therefore our results suggest that polyphenol-mediated regulation of GSH levels could modulate cellular response in intestinal cells. Moreover, some flavonoids behave as natural inhibitors of GlxI [ 63 ].…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, in the same cell model, we studied the effect of apple polyphenols. The interest of the study is supported by literature data which demonstrate the ability of some polyphenols to modulate glyoxalase activity, oxidative and dicarbornyl stress as shown in different experimental models [22][23][24][25].…”
Section: Introductionmentioning
confidence: 86%
“…However, at high doses, it may produce toxic and carcinogenic effects in healthy cells. The cytotoxic effects observed after curcumin treatment may be due to post-translational modifications of histones, which lead to modifications in gene expression [13]. Additionally, a diet rich in fat can be associated with hypermethylation of specific DNA promoters of tumor suppressor genes [14].…”
Section: Epigenetic and Genetic Mechanisms For The Regulation Of Genementioning
confidence: 99%